Deterministic processes shape bacterial community assembly in a karst river across dry and wet seasons - Wu, Yongjie; Zhang, Yang; Yang, Xueqin; Li, Kaiming; Mai, Bixian; He, Zhili; Wu, Renren (Frontiers in Microbiology, 2022)
Karst rivers are particularly vulnerable to bacterial pollution because immigrations are easily diffused from the surrounding environments due to their strong hydraulic connectivity. However, the assembly mechanism in shaping riverine bacterial biogeography is still poorly understood, especially for an ecosystem in karst area. Here, 16S rRNA gene were used to explore the spatiotemporal and biogeographical patterns of bacterial communities from the Chishui River in the dry and wet seasons, and explore the impact of external immigrations on the assembly of water bacterial community. Our results showed clear spatiotemporal patterns of bacterial communities with a more pronounced seasonal rather than spatial fluctuation, which appeared to be dependent on the seasonal-related environmental factors (e.g., temperature, turbidity). The bacterial communities exhibited a significant (p < 0.05) distance-decay pattern in both seasons, and it had a stronger distance-decay relationship in the dry season than in the wet season. However, most of the biomarkers of different external immigrations did not show significant (p > 0.05) distance-decay patterns along the Chishui river, implying that the biomarkers could be used as indicators of external immigrations (e.g., OTU_125, OTU_536). Also, the tributaries were the mainly external immigration (20.44% ~ 83.68%) for the Chishui River, while other terrestrial immigration (e.g., livestock, soil of the cropland, brewing wastewater treatment plant, sewages) showed relatively little influence, which could be due to the hydrodynamic conditions (e.g., fragile rock-soil system, hydrological structure) of the karst river. Additionally, the assembly of water bacterial communities in the Chishui river was governed by more determinism (50.7% ~ 85.7%) than stochasticity (14.3% ~ 49.3%) in both the dry and wet seasons. We demonstrated that the bacterial community substantial variations are largely shaped by deterministic processes, thereby providing a better understanding of spatiotemporal patterns and mechanisms of bacterial community in a karst river waters.